2022
DOI: 10.24036/patriot.v4i1.821
|View full text |Cite
|
Sign up to set email alerts
|

Kekuatan Otot Bahu dan Daya Ledak Otot Lengan: Apakah Memiliki Korelasi dengan Servis Atas Sitting Volleyball?

Abstract: Terjadi penurunan kondisi fisik pada atlet bola voli Paralympic Indonesia secara drastis di era saat ini, sehingga hal tersebut berdampak kepada penurunan performa atlet khususnya berkaitan dengan servis atas. Oleh karena itu, penelitian ini bertujuan untuk menganalisis korelasi antara kekuatan otot bahu dan daya ledak otot lengan terhadap keterampilan servis atas atlet bola voli duduk Paralimpiade Indonesia. Pendekatan penelitian kuantitatif dengan metode deskriptif korelasional yang digunakan dalam penelitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Furthermore, the results of the study (Ridwan, 2020) thus, the players are expected to be more motivated to do physical exercise as needed. (Whinata Kardiyanto & Setiawan, 2022) concluded that to have an optimal upper serve, athletes must pay attention to the physical condition factors of shoulder muscle strength and arm muscle explosiveness, because these two aspects contribute significantly to upper serve performance. With maximum physical condition, it is expected that the athlete's performance can improve even better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the results of the study (Ridwan, 2020) thus, the players are expected to be more motivated to do physical exercise as needed. (Whinata Kardiyanto & Setiawan, 2022) concluded that to have an optimal upper serve, athletes must pay attention to the physical condition factors of shoulder muscle strength and arm muscle explosiveness, because these two aspects contribute significantly to upper serve performance. With maximum physical condition, it is expected that the athlete's performance can improve even better.…”
Section: Discussionmentioning
confidence: 99%
“…Physical condition in volleyball is the basic foundation for athletes to show their performance in matches (Hamdan, 2020). Volleyball athletes who have a high physical condition will be able to overcome and be ready for the match, have good thinking power in high concentration in the match, so that every volleyball athlete who has a prime physique can bring out his maximum ability both in terms of technique, tactics or mentality (Whinata Kardiyanto & Setiawan, 2022). Physical condition is a necessity that is needed.…”
Section: Introductionmentioning
confidence: 99%